Reimagining Wearable Electronic Devices with Nonvolatile Gel Electrolytes - Owyeung, Rachel. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisors: Sameer Sonkusale, and Matthew Panzer.; Committee: Hyunmin Yi, and Trisha Andrew.; Keywords: Chemical engineering, and Materials Science.